1994
DOI: 10.1090/dimacs/015/03
|View full text |Cite
|
Sign up to set email alerts
|

Application of computational tools for finitely presented groups

Abstract: Computer based techniques for recognizing finitely presented groups are quite powerful. Tools available for this purpose are outlined. They are available both in stand-alone programs and in more comprehensive systems.A general computational approach for investigating finitely presented groups by way of quotients and subgroups is described and examples are presented. The techniques can provide detailed information about group structure. Under suitable circumstances a finitely presented group can be shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Effective algorithms for determining p-quotients were originated by the work of Macdonald (1973Macdonald ( , 1974. His techniques were later extended by Wamsley (1974), Bayes et al (1974), Newman (1976) and Havas and Newman (1980). Nickel (1994) developed and implemented an algorithm to compute the nilpotent quotients for finitely presented groups.…”
Section: Definition 13 Given a Finite Presentation Of A Group G A mentioning
confidence: 99%
See 2 more Smart Citations
“…Effective algorithms for determining p-quotients were originated by the work of Macdonald (1973Macdonald ( , 1974. His techniques were later extended by Wamsley (1974), Bayes et al (1974), Newman (1976) and Havas and Newman (1980). Nickel (1994) developed and implemented an algorithm to compute the nilpotent quotients for finitely presented groups.…”
Section: Definition 13 Given a Finite Presentation Of A Group G A mentioning
confidence: 99%
“…Computing nilpotent quotients is also covered in depth in Chapter 11 of Sims (1994). Research on determining finite solvable quotients can be found in Plesken (1987), Niemeyer (1994), Wegner (1992) and Havas and Robertson (1994). As for determining polycyclic quotients, in 1981, Baumslag, et al described a polycyclic quotient algorithm in Baumslag et al (1981a) and Baumslag et al (1981b).…”
Section: Definition 13 Given a Finite Presentation Of A Group G A mentioning
confidence: 99%
See 1 more Smart Citation
“…The Reidemeister rewriting allows us to rewrite the relations of the group to relations of the subgroup [16,31,21]. Note that a method to compute a finite presentation for a finite index subgroup can be applied in the investigation of the structure of a group by its finite index subgroups; see [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our proof of Theorem 1.1 is constructive and it yields a finite L-presentation for the subgroup. These finite L-presentations can be applied in the investigation of the underlying groups as the methods in [17] suggest for finitely presented groups. Notice that Theorem 1.1 was already posed in Proposition 2.9 of [1].…”
Section: Introductionmentioning
confidence: 99%